Increased NFAT and NFκB signalling contribute to the hyperinflammatory phenotype in response to Aspergillus fumigatus in a mouse model of cystic fibrosis. - Amelia Bercusson; Thomas J Williams; Nicholas J Simmonds; Eric Wfw Alton; Uta Griesenbach; Anand Shah; Adilia Warris; Darius Armstrong-James (PLoS Pathogens)
Aspergillus fumigatus (Af) is a major mould pathogen found ubiquitously in the air. It commonly infects the airways of people with cystic fibrosis (CF) leading to Aspergillus bronchitis or allergic bronchopulmonary aspergillosis. Resident alveolar macrophages and recruited neutrophils are important first lines of defence for clearance of Af in the lung. However, their contribution to the inflammatory phenotype in CF during Af infection is not well understood. Here, utilising CFTR deficient mice we describe a hyperinflammatory phenotype in both acute and allergic murine models of pulmonary aspergillosis. We show that during aspergillosis, CFTR deficiency leads to increased alveolar macrophage death and persistent inflammation of the airways in CF, accompanied by impaired fungal control. Utilising CFTR deficient murine cells and primary human CF cells we show that at a cellular level there is increased activation of NFκB and NFAT in response to Af which, as in in vivo models, is associated with increased cell death and reduced fungal control. Taken together, these studies indicate that CFTR deficiency promotes increased activation of inflammatory pathways, the induction of macrophage cell death and reduced fungal control contributing to the hyper-inflammatory of pulmonary aspergillosis phenotypes in CF.